A tale of two countries: adapting Chinese leadership styles to a South African context - Zhou, Ying (Graduate School of Business (GSB), 2021)
The status of multinational organisations continues to expand, as global opportunities increase. In particular, Chinese manufacturing companies continue to grow and expand overseas. Given the fact that Chinese Paternalistic Leadership performed by Chinese managers is rooted in Chinese culture, that is different from that practised in other countries of the world. Cross-cultural acumen plays a vital role in leadership success or failure in globalizing organizations. Without cultural adaptation, Chinese managers would be less effective and efficient, when dealing with employees from other cultural backgrounds. Thus, there appears to be a need for the adaptation of Chinese leadership, in order to optimize the outcomes of leadership in the organization in various multicultural settings. This study posits a new research context for Chinese Paternalistic Leadership; and it attempts to explore the question of the leadership-adaptation challenges of Chinese managers, working in a South African Zulu cultural context. The study has used a mixed-methods research approach to collect the data, and for the analysis thereof. Quantitative data were collected by means of surveys from Chinese workers and South African Zulu workers, who were working in Chinese clothing factories – in order to compare their cultural values and perceptions of Chinese leadership behaviours. Qualitative data were collected by semistructured, in-depth interviews with Chinese managers, who were the leaders of Zulu subordinates, in order to investigate their cross-cultural experiences and perspectives. The results from the cultural-values survey data confirmed the distinct differences of cultural dimensions: Power Distance (PDI), Individualism (IDV), Uncertainty Avoidance (UAI), Masculinity (MAS) and Long-Term versus ShortTerm Orientation (LTO) between Chinese and Zulu people. Additionally, no significant difference between the two groups was found on Indulgence versus Restraint (IVR). When compared with Chinese people, the Zulu people hold the characteristics of being low in power distance, collectivism, feminism, high in uncertainty avoidance, short-term orientation, and restraint. On the perceived leadership behaviours scale, the differences between Chinese and Zulu people were shown in all the three dimensions of Chinese leadership behaviours. Compared with Chinese employees, Zulu employees perceived Chinese leadership behaviours as being high on authoritarian leadership behaviour, but low on benevolent and moral leadership behaviour. In addition, it was proved that culture caused different perceptions of authoritarian leadership behaviour in relation to power distance. In interviews, Chinese managers overwhelmingly indicated that the characteristics of Zulu employees were very different from those of Chinese employees. Meanwhile, the Chinese managers confessed that they were confronted with difficulties and challenges in South Africa, including communication barriers, legal constraints, and differences in collective relationships and work ethic. However, they recognised that they were in a different culture, and have identified the need to adjust their leadership behaviours. The participants suggested that they have made progress in establishing relationships, and in improving communication with the Zulu employees. Overall, this study concluded with a discussion of the various strategies for the adaptation of Chinese leadership styles concerning authority/decision-making, relationships and communication in authoritarian leadership styles, benevolent leadership styles, and moral leadership styles respectively. The outcomes of this study are expected to contribute to the theories of Chinese leadership, as well as to Chinese-management practices in South Africa. Nevertheless, future research is recommended, in order to validate the current results, and also to further explore various issues that are beyond the scope of this study.